Memórias em disputa: transformando modos de vida no sertão e na cidade - Rodrigues, Rejane Meireles Amaral (2011)
This these presents as main objective to understand the paradoxal issve shown by the press, in the early XX century, regarding the status of today s city of Montes Claros . Where the press in sometimes called Montes Claros big city in others in was called small town. This search comes out of the misunderstanding. Still caused by the media of the city of Montes Claros when approaching this matter. The elaboration of this these was based on the informations extracted from the main newspapers from the local press of that time. They are the following: Montes Claros ( editions from 1916 to 1920) . On the other Hans in order to support the debate, and also verify the elements involved with the fows of this search. I took as source of information the following documents: Coleção Sesquicentenária, Relatórios da secretaria de agricultura, diretoria de industria a comércio( from 1910 to 1922), and the library of Câmara Municipal de Montes Claros . I showed how the conflict small town versus big city was getting stronger by the work of the local press. Being the newspaper dubious and lacking clearness in its articles as for the vocabulary used in its publications is wide-raging and complex. It conveys the reality which is alone complex. My intention was to perceive how the press of Montes Claros built. On its newspaper s lives of this region. For this I picked up some events such as: The construction of Ramal de Montes Claros , linha de tiro , construction of public buildings, and laying of pavements on streets and squares. The press considered these events to be fundamental for the city existence. In order to stop believing the history of the history of the city was built by the press ones need to understand that this history was made up by the political parties those newspapers standed for. I believe the alternation of the categories city and countryside. Considering them to be appropriate for the political parties to state their interests and, there for, giving possibilities for further searches.